El humanismo de Illich, evaluación de tecnologías para una sociedad convivencial - Aimino, Matías (ARFIL y UNL, 2018)
Illich’s criticism of contemporary industrial societies involves, among otherthings, a new conception of technology assessment based on the philosophical notionof “conviviality”. The purpose of this paper is to reconstruct such conception, whosemost salient features are radical pluralism, technologic constructivism and humanism, that is,the idea that the best yardstick to measure actual or potential